Why Australia needs to define obesity as a chronic condition - C. A. Opie; H. M. Haines; K. E. Ervin; K. Glenister; D. Pierce (BMC, 2017)
Abstract Background In Australia people with a diagnosed chronic condition can be managed on unique funded care plans that allow the recruitment of a multidisciplinary team to assist in setting treatment goals and adequate follow up. In contrast to the World Health Organisation, the North American and European Medical Associations, the Australian Medical Association does not recognise obesity as a chronic condition, therefore excluding a diagnosis of obesity from qualifying for a structured and funded treatment plan. Body The Australian guidelines for management of Obesity in adults in Primary Care are structured around a five step process -the '5As': Ask & Assess, Advise, Assist and Arrange'. This article aims to identify the key challenges and successes associated with the '5As' approach, to better understand the reasons for the gap between the high Australian prevalence of overweight and obesity and an actual diagnosis and treatment plan for managing obesity. It argues that until the Australian health system follows the international lead and defines obesity as a chronic condition, the capacity for Australian doctors to diagnose and initiate structured treatment plans will remain limited and ineffective. Conclusion Australian General Practitioners are limited in their ability manage obesity, as the current treatment guidelines only recognise obesity as a risk factor rather than a chronic condition.